Composition for TPO functional master batch, TPO functional master batch and preparation method thereof, composition for waterproof coiled material, waterproof coiled material and preparation method thereof

By using a composition containing TPO elastomer, polyethylene or polypropylene, polar monomer, metal salt, crosslinking agent, calcium stearate and stearic acid in the TPO waterproof coil, the problem of poor thermal stability and dimensional stability of the TPO waterproof coil is solved by using physical crosslinking and non-covalent bond crosslinking networks, and excellent thermal stability and dimensional stability are achieved.

CN119823514AActive Publication Date: 2025-04-15KUNSHAN KESHUN WATERPROOF MATERIAL
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411817369.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-15
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The thermal stability and dimensional stability of existing TPO waterproof coils are poor, resulting in the prone to thermal oxygen aging and welding edge failure under long-term high or low temperature alternating conditions.

Method used

A TPO functional masterbatch composition is adopted, which contains TPO elastomer, polyethylene or polypropylene, polar monomer, metal salt, crosslinking agent, calcium stearate and stearic acid. The stability of the molecular chain in the microstructure in the matrix is ​​enhanced by combining physical crosslinking and non-covalent bond crosslinking networks.

Benefits of technology

It effectively improves the thermal stability and dimensional stability of TPO waterproof coils, reduces the probability of material agglomeration, guarantees product performance, and achieves good thermal stability and dimensional stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182180450000091
    Figure BDA0005182180450000091
  • Figure BDA0005182180450000101
    Figure BDA0005182180450000101
  • Figure BDA0005182180450000131
    Figure BDA0005182180450000131
Patent Text Reader

Abstract

The invention relates to the technical field of TPO waterproof coiled materials, and discloses a TPO functional master batch composition, a TPO functional master batch, a preparation method of the TPO functional master batch, a waterproof coiled material composition, a waterproof coiled material and a preparation method of the waterproof coiled material. The composition for the TPO functional master batch contains a TPO elastomer, a first component, a second component, metal salt, a cross-linking agent, stearic acid and calcium stearate, relative to 100 parts by weight of the TPO elastomer, the content of the first component is 10-20 parts by weight, the content of the second component is 1-5 parts by weight, the content of the metal salt is 2-8 parts by weight, the content of the cross-linking agent is 0.1-1.5 parts by weight, and the total content of the calcium stearate and the stearic acid is 0.5-3 parts by weight; the TPO functional master batch obtained by adopting the composition for the TPO functional master batch provided by the invention has a good application prospect in preparation of TPO waterproof coiled materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of TPO waterproof coiled materials, and in particular to a composition for TPO functional masterbatch, a TPO functional masterbatch and a preparation method thereof, a composition for waterproof coiled materials, a waterproof coiled material and a preparation method thereof. Background Art

[0002] Thermoplastic polyolefin (TPO) is a copolymer formed with ethylene and propylene as the main materials. Because its molecular chain is saturated, the content of tertiary carbon atoms is relatively small, and it does not contain polar atoms, it has a certain chemical stability.

[0003] In addition, TPO material has the advantages of low density and good low-temperature toughness, and has the good processing performance of plastics and the excellent toughness of rubber, and can be processed using conventional equipment. TPO material is a new material with good application prospects, especially suitable for use in the field of waterproof membranes.

[0004] When TPO waterproof membrane made of TPO material is used for exposed single-layer roof, it is usually exposed to long-term high temperature or alternating high and low temperature conditions. If the thermal stability of the product is insufficient, thermal oxidation aging may occur in a short period of time; or the welding edge may fail due to poor dimensional stability of the waterproof membrane (excessive dimensional change rate), leading to failure of the waterproof project.

[0005] Therefore, thermal stability and dimensional stability are key technical indicators in the development and application of TPO waterproof membranes.

[0006] At present, chemical cross-linking, adding inorganic fillers or adding organic rigid fillers are usually used to improve the stability of TPO waterproof membranes.

[0007] The use of chemical cross-linking to form a molecular chain network inside the TPO matrix can effectively improve the overall stability of the material, but this technical route has low controllability and is prone to problems in the actual process.

[0008] Although the thermal stability and dimensional stability of TPO waterproof membrane can be improved to a certain extent by adding inorganic fillers, in actual production, the fillers are prone to agglomeration, resulting in poor improvement effects and a serious decrease in the elongation at break of TPO waterproof membrane.

[0009] By adding organic rigid fillers into the formula, the overall stability of the TPO waterproof membrane obtained still needs to be improved.

[0010] Therefore, it is of great significance to develop a TPO waterproof membrane with good thermal stability and dimensional stability. Summary of the invention

[0011] The purpose of the present invention is to overcome the problem of poor thermal stability and dimensional stability of TPO waterproofing membrane in the prior art.

[0012] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composition for TPO functional masterbatch, which contains a TPO elastomer, a first component, a second component, a metal salt, a crosslinking agent, calcium stearate and stearic acid;

[0013] Relative to 100 parts by weight of the TPO elastomer, the content of the first component is 10-20 parts by weight, the content of the second component is 1-5 parts by weight, the content of the metal salt is 2-8 parts by weight, the content of the cross-linking agent is 0.1-1.5 parts by weight, and the total content of the calcium stearate and the stearic acid is 0.5-3 parts by weight;

[0014] The first component is polyethylene and / or polypropylene, the polyethylene has a melt index of 0.1-2.5 g / 10 min at 190° C. and a load of 2.16 kg, and the polypropylene has a melt index of 1.5-3.5 g / 10 min at 230° C. and a load of 2.16 kg;

[0015] The second component is selected from polar monomers containing any one of hydroxyl, carboxyl and amino groups;

[0016] The metal salt is selected from at least one of zinc acetate, zinc trifluoromethanesulfonate and ferric chloride;

[0017] The mass ratio of the calcium stearate to the stearic acid is 1:0.16-6.

[0018] The second aspect of the present invention provides a method for preparing a TPO functional masterbatch, the method comprising: granulating a mixed material to obtain the TPO functional masterbatch;

[0019] The mixed material is the material obtained by mixing the components in the composition described in the first aspect.

[0020] The third aspect of the present invention provides a TPO functional masterbatch prepared by the method described in the second aspect.

[0021] The fourth aspect of the present invention provides a composition for TPO waterproofing coiled material, the composition comprising TPO elastomer, TPO functional masterbatch, masterbatch, antioxidant and light stabilizer;

[0022] Relative to 100 parts by weight of the TPO elastomer, the content of the TPO functional masterbatch is 5-40 parts by weight, the content of the masterbatch is 1-6 parts by weight, the content of the antioxidant is 0.3-1 parts by weight, and the content of the light stabilizer is 0.5-2 parts by weight;

[0023] The TPO functional masterbatch is the TPO functional masterbatch described in the third aspect above.

[0024] A fifth aspect of the present invention provides a method for preparing a TPO waterproof membrane, the method comprising:

[0025] (1) contacting and stirring the composition described in the fourth aspect to obtain a mixture;

[0026] (2) Extruding the mixture to obtain the TPO waterproof membrane.

[0027] The sixth aspect of the present invention provides a waterproof roll material prepared by the method described in the fifth aspect.

[0028] The components in the TPO functional masterbatch composition provided by the present invention are combined with each other through physical crosslinking based on factors such as van der Waals forces and non-covalent crosslinking networks based on electrostatic forces, thereby effectively improving the stability of molecular chains in the microstructure within the matrix.

[0029] The TPO functional masterbatch prepared by using the composition for TPO functional masterbatch provided by the present invention has good application prospects in the preparation of TPO waterproof membrane.

[0030] The components in the composition for TPO waterproof coiled material provided by the present invention have excellent compatibility, and after blending, the probability of material agglomeration can be effectively reduced, thereby effectively ensuring product performance.

[0031] The TPO waterproof roll material prepared by using the composition for TPO waterproof roll material provided by the invention has good thermal stability and dimensional stability. DETAILED DESCRIPTION

[0032] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0033] As mentioned above, the first aspect of the present invention provides a composition for TPO functional masterbatch, which contains a TPO elastomer, a first component, a second component, a metal salt, a crosslinking agent, calcium stearate and stearic acid;

[0034] Relative to 100 parts by weight of the TPO elastomer, the content of the first component is 10-20 parts by weight, the content of the second component is 1-5 parts by weight, the content of the metal salt is 2-8 parts by weight, the content of the cross-linking agent is 0.1-1.5 parts by weight, and the total content of the calcium stearate and the stearic acid is 0.5-3 parts by weight;

[0035] The first component is polyethylene and / or polypropylene, the polyethylene has a melt index of 0.1-2.5 g / 10 min at 190° C. and a load of 2.16 kg, and the polypropylene has a melt index of 1.5-3.5 g / 10 min at 230° C. and a load of 2.16 kg;

[0036] The second component is selected from polar monomers containing any one of hydroxyl, carboxyl and amino groups;

[0037] The metal salt is selected from at least one of zinc acetate, zinc trifluoromethanesulfonate and ferric chloride;

[0038] The mass ratio of the calcium stearate to the stearic acid is 1:0.16-6.

[0039] Preferably, the mass ratio of the calcium stearate to the stearic acid is 1:0.5-1.5. The inventors of the present invention have found that in this preferred case, the obtained TPO functional masterbatch is applied to the preparation of TPO waterproofing membrane, so that the stability of the TPO waterproofing membrane is better.

[0040] Preferably, the melt mass flow rate of the TPO elastomer at 230°C and under a load of 2.16 kg is 0.5-15 g / 10 min. The inventors of the present invention have found that in this preferred case, the TPO functional masterbatch obtained by extrusion granulation is applied to the TPO waterproof membrane formula, which can make the TPO waterproof membrane more stable.

[0041] Preferably, the polyethylene has a density of not less than 0.941-0.960 g / cm 3 High-density polyethylene and / or density not higher than 0.93g / cm 3 of linear low density polyethylene.

[0042] Preferably, the cross-linking agent is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide and dibenzoyl peroxide.

[0043] Preferably, the second component is selected from at least one of maleic anhydride, glycidyl methacrylate and hydroxyethyl methacrylate.

[0044] As mentioned above, the second aspect of the present invention provides a method for preparing TPO functional masterbatch, the method comprising:

[0045] Granulating the mixture to obtain the TPO functional masterbatch;

[0046] The mixed material is a material obtained by mixing the various components in the composition described in the first aspect above.

[0047] Preferably, the kneading process is carried out in an extruder.

[0048] Preferably, the conditions of the granulation treatment include: a temperature of 170-220° C. and a screw speed of 15-45 rpm.

[0049] As mentioned above, the third aspect of the present invention provides a TPO functional masterbatch prepared by the method described in the second aspect.

[0050] As mentioned above, the fourth aspect of the present invention provides a composition for TPO waterproofing membrane, the composition comprising TPO elastomer, TPO functional masterbatch, masterbatch, antioxidant and light stabilizer;

[0051] Relative to 100 parts by weight of the TPO elastomer, the content of the TPO functional masterbatch is 5-40 parts by weight, the content of the masterbatch is 1-6 parts by weight, the content of the antioxidant is 0.3-1 parts by weight, and the content of the light stabilizer is 0.5-2 parts by weight;

[0052] The TPO functional masterbatch is the TPO functional masterbatch described in the third aspect above.

[0053] Preferably, relative to 100 parts by weight of the TPO elastomer, the content of the TPO functional masterbatch is 10-25 parts by weight, the content of the masterbatch is 2-4 parts by weight, the content of the antioxidant is 0.5-1 part by weight, and the content of the light stabilizer is 1-2 parts by weight.

[0054] Preferably, the TPO elastomer is an ethylene-α-olefin copolymer and / or a propylene-α-olefin copolymer; more preferably, the TPO elastomer is selected from at least one of Basel CA10A, Basel CA60A, and Sino-Korea Petrochemical NS06.

[0055] The antioxidant is selected from at least one of antioxidant 1010 , antioxidant 1076 and antioxidant 168 .

[0056] The light stabilizer is selected from at least one of light stabilizer 770, light stabilizer 2020, UV-531, UV-326, and UV-327.

[0057] As mentioned above, the fifth aspect of the present invention provides a method for preparing a TPO waterproof membrane, the method comprising:

[0058] (1) contacting and stirring the components of the composition described in the fourth aspect to obtain a mixture;

[0059] (2) Extruding the mixture to obtain the TPO waterproof membrane.

[0060] Exemplarily, the contact stirring can be performed in a high-speed mixer.

[0061] Preferably, in step (1), the contact stirring conditions include: temperature of 20-35° C., rotation speed of 300-1000 rpm, and time of 20-40 min.

[0062] Preferably, in step (2), the extrusion molding conditions include: extruder temperature of 145-225° C., screw speed of 10-40 rpm, and line speed of 2-6 m / min.

[0063] Preferably, the method further comprises: calendering, pulling and winding the material obtained by the extrusion molding in sequence.

[0064] The present invention has no special requirements for the conditions of the calendering, the pulling and the winding, and those skilled in the art can select them within the known parameter range in the art as needed.

[0065] As mentioned above, the sixth aspect of the present invention provides a waterproof roll material prepared by the method described in the fifth aspect.

[0066] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the instruments and raw materials used are commercially available.

[0067] TPO Elastomer:

[0068] Elastomer I-1: Sino-Korea Petrochemical NS06, with a melt mass flow rate of 0.7 g / 10 min at 230° C. and a load of 2.16 kg, purchased from Wuhan Sino-Korea Petrochemical Company, and manufactured by Sino-Korea Petrochemical Company.

[0069] Elastomer I-2: Basel CA10A, with a melt mass flow rate of 0.6 g / 10 min at 230° C. and a load of 2.16 kg, purchased from Shanghai Changshi Plastics Co., Ltd., and manufactured by LyondellBasell Industries of the Netherlands.

[0070] Elastomer I-3: Basell CA60A, with a melt mass flow rate of 14 g / 10 min at 230° C. and a load of 2.16 kg, purchased from Shanghai Changshi Plastic Chemical Co., Ltd., and manufactured by LyondellBasell Industries.

[0071] First component:

[0072] Linear low-density polyethylene: LLDPE, density 0.919 g / cm3, melt index 2.1 g / 10 min at 190 ° C and 2.16 kg load, purchased from ExxonMobil, brand ExxonMobil TM LD 2119.LN Molding.

[0073] High-density polyethylene: HDPE, density is 0.946g / cm 3 The melt index is 0.18 g / 10 min at 190°C and 2.16 kg load. It was purchased from Saudi Chevron Phillips Company with the brand name TR144.

[0074] Polypropylene:

[0075] Homopolymer polypropylene (PPH), with a melt index of 2.8 g / 10 min at 230 °C and a load of 2.16 kg, was purchased from ExxonMobil Corporation under the brand name ExxonMobil TM PP4712E1.

[0076] Impact polypropylene (PPB), with a melt index of 2.5 g / 10 min at 230° C. and a load of 2.16 kg, was purchased from Dushanzi Petrochemical Company of PetroChina Co., Ltd. with a brand name of K8003.

[0077] Second component:

[0078] Second component I-1: 2,3-epoxypropyl methacrylate.

[0079] Second component I-2: maleic anhydride.

[0080] Second component I-3: hydroxyethyl methacrylate.

[0081] The second component II: triphenyl acrylonitrile, purchased from Shanghai MacLean Company, brand number T970426.

[0082] Metal salts:

[0083] Metal salt I-1: ferric chloride.

[0084] Metal salt I-2: zinc acetate.

[0085] Metal salt I-3: zinc trifluoromethanesulfonate.

[0086] Metal Salt II: Barium Sulfate

[0087] Crosslinking agent:

[0088] Cross-linking agent I-1: dibenzoyl peroxide.

[0089] Cross-linking agent I-2: dicumyl peroxide.

[0090] Crosslinking agent I-3: di-tert-butyl peroxide.

[0091] Calcium carbonate: heavy calcium carbonate, purchased from OMYA (Shanghai) Investment Co., Ltd., brand OMYACARB 5.

[0092] Cross-linked polystyrene microspheres: particle size D50 is 3 μm, purchased from Dongguan Kemai New Materials Co., Ltd., brand KM-503.

[0093] Antioxidants:

[0094] Antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) was purchased from BASF (China) Co., Ltd. with the brand name Irganox1010.

[0095] Light Stabilizer:

[0096] Light stabilizer 2020 (bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine) was purchased from BASF (China) Co., Ltd. with the brand name Irganox2020.

[0097] Masterbatch: White masterbatch, purchased from Henan Ruying Chemical Products Co., Ltd., model number is “extra white masterbatch”.

[0098] Different raw material formulations are used in the following examples of the present invention. The amounts of raw materials are all parts by weight unless otherwise specified, and each part by weight represents 100 g.

[0099] The following preparation examples and comparative preparation examples are used to illustrate that the composition for TPO functional masterbatch of the present invention is prepared according to the formula in Table 1 and the TPO functional masterbatch is prepared according to the following method.

[0100] Preparation Example 1

[0101] The mixed material obtained by mixing the components in formula 1 is kneaded in an extruder, and the mixed material is granulated to obtain the TPO functional masterbatch, which is named TPO functional masterbatch L1;

[0102] The temperature of the granulation treatment was 180°C and the screw speed was 30 rpm.

[0103] The other preparation examples and comparative preparation examples were all carried out using a method similar to that of Preparation Example 1, except that the formulas were different, as shown in Table 1.

[0104] Table 1

[0105]

[0106] Table 1

[0107]

[0108] Example 1

[0109] This example is used to illustrate the formulation of the composition for TPO waterproof membrane in Table 2, and to prepare TPO waterproof membrane according to the following method.

[0110] (1) contacting and stirring the composition for TPO waterproof membrane in a high-speed mixer to obtain a mixture;

[0111] (2) extruding the mixture, and then calendering, pulling and rolling the material obtained by extrusion molding in sequence to obtain the TPO waterproof membrane;

[0112] The contact stirring temperature was 23°C, the rotation speed was 800 rpm, and the time was 30 min.

[0113] Unless otherwise specified, Examples 2 to 4 are all carried out using a method similar to that of Example 1, with the differences being the formulations and process parameters, as shown in Table 2.

[0114] Table 2

[0115] Example 1 Example 2 Example 3 Example 4 TPO elastomer type Elastomer I-1 Elastomer I-2 Elastomer I-3 Same as Example 1 Dosage / weight 100 100 100 100 TPO functional masterbatch type L1 L2 L3 L4 Dosage / weight 22.2 12.5 33.3 5 color masterbatch Dosage / weight 2.2 2.5 2.2 2 Antioxidants Dosage / weight 0.56 0.625 0.56 0.5 Light Stabilizer Dosage / weight 1.12 1.3 1.12 1.5 Extrusion Temperature / ℃ 180 160 190 210 Screw speed / rpm 20 10 20 30 Line speed / (m / min) 4 4 5 6

[0116] Example 5

[0117] This example is carried out in a similar manner to that of Example 1, except that this example uses an equal weight portion of TPO functional masterbatch L5 to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0118] Comparative Example 1

[0119] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of calcium carbonate is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0120] Comparative Example 2

[0121] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of cross-linked polystyrene microspheres is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0122] Comparative Example 3

[0123] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of TPO functional masterbatch L-D1 is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0124] Comparative Example 4

[0125] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of TPO functional masterbatch L-D2 is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0126] Comparative Example 5

[0127] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of TPO functional masterbatch L-D3 is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0128] Comparative Example 6

[0129] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of TPO functional masterbatch L-D4 is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0130] Comparative Example 7

[0131] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of TPO functional masterbatch L-D5 is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0132] Comparative Example 8

[0133] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of TPO functional masterbatch L-D6 is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0134] Comparative Example 9

[0135] This comparative example is carried out in a similar manner to Example 1, except that an equal weight portion of TPO functional masterbatch L-D7 is used to replace the TPO functional masterbatch L1 in Example 1, and the rest is the same as Example 1 to prepare a TPO waterproof membrane.

[0136] Test Case

[0137] The performance of the TPO waterproof membrane prepared in the above example was tested according to the method specified in GB / T 27789-2011, and the results are shown in Table 3;

[0138] Mechanical property retention rate (tensile strength retention rate and elongation at break retention rate) of TPO waterproof membrane after thermal aging treatment (temperature 115℃, time 56 days) and weight loss 5wt% corresponding temperature T 5% (Thermogravimetric analysis method, test atmosphere: air, heating rate of 10℃ / min, temperature range of 25℃ to 600℃) represents the thermal stability of TPO waterproof membrane;

[0139] Tensile strength retention rate = tensile strength after heat aging / tensile strength without treatment * 100%;

[0140] Retention rate of elongation at break = retention rate of elongation at break after heat aging / retention rate of elongation at break without treatment * 100%;

[0141] Longitudinal dimensional change rate = longitudinal length after heat treatment / longitudinal length before heat aging*100%.

[0142] Table 3

[0143]

[0144]

[0145] From the above results, it can be seen that the TPO functional masterbatch obtained by using the composition for TPO functional masterbatch provided by the present invention has excellent application prospects in the field of TPO waterproof membranes. The TPO waterproof membrane prepared by using the composition for TPO waterproof membrane provided by the present invention has excellent thermal stability and low dimensional change rate, while also taking into account good elongation at break, and achieves a good balance effect in terms of strength, toughness and stability.

[0146] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composition for TPO functional masterbatch, characterized in that: The composition contains TPO elastomer, a first component, a second component, a metal salt, a crosslinking agent, calcium stearate and stearic acid; Relative to 100 parts by weight of the TPO elastomer, the content of the first component is 10-20 parts by weight, the content of the second component is 1-5 parts by weight, the content of the metal salt is 2-8 parts by weight, the content of the cross-linking agent is 0.1-1.5 parts by weight, and the total content of the calcium stearate and the stearic acid is 0.5-3 parts by weight; The first component is polyethylene and / or polypropylene, the polyethylene has a melt index of 0.1-2.5 g / 10 min at 190° C. and a load of 2.16 kg, and the polypropylene has a melt index of 1.5-3.5 g / 10 min at 230° C. and a load of 2.16 kg; The second component is selected from polar monomers containing any one of hydroxyl, carboxyl and amino groups; The metal salt is selected from at least one of zinc acetate, zinc trifluoromethanesulfonate and ferric chloride; The mass ratio of the calcium stearate to the stearic acid is 1:0.16-6.

2. The composition according to claim 1, wherein The mass ratio of the calcium stearate to the stearic acid is 1:0.5-1.

5.

3. The composition according to claim 1 or 2, wherein The melt mass flow rate of the TPO elastomer at 230° C. and under a load of 2.16 kg is 0.5-15 g / 10 min; And / or, the polyethylene is a high-density polyethylene having a density not less than 0.941-0.960 g / cm3 and / or a linear low-density polyethylene having a density not more than 0.93 g / cm3; And / or, the cross-linking agent is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide and dibenzoyl peroxide; And / or, the second component is selected from at least one of maleic anhydride, glycidyl methacrylate and hydroxyethyl methacrylate.

4. A method for preparing TPO functional masterbatch, characterized in that: The method includes: Granulating the mixture to obtain the TPO functional masterbatch; The mixed material is a material obtained by mixing the components in the composition according to any one of claims 1 to 3.

5. The method according to claim 4, wherein: The conditions of the granulation treatment include: a temperature of 170-220° C. and a screw speed of 15-45 rpm.

6. TPO functional masterbatch prepared by the method according to claim 4 or 5.

7. A composition for TPO waterproofing membrane, characterized in that: The composition contains TPO elastomer, TPO functional masterbatch, color masterbatch, antioxidant and light stabilizer; Relative to 100 parts by weight of the TPO elastomer, the content of the TPO functional masterbatch is 5-40 parts by weight, the content of the masterbatch is 1-6 parts by weight, the content of the antioxidant is 0.3-1 parts by weight, and the content of the light stabilizer is 0.5-2 parts by weight; The TPO functional masterbatch is the TPO functional masterbatch according to claim 6.

8. A method for preparing a TPO waterproofing membrane, characterized in that: The method includes: (1) contacting and stirring the components of the composition according to claim 7 to obtain a mixture; (2) Extruding the mixture to obtain the TPO waterproof membrane.

9. The method according to claim 8, wherein: In step (1), the contact stirring conditions include: temperature of 20-35°C, rotation speed of 300-1000 rpm, and time of 20-40 min; And / or, in step (2), the extrusion molding conditions include: extruder temperature of 145-225°C, screw speed of 10-40rpm, and line speed of 2-6m / min.

10. The waterproof coiled material prepared by the method according to claim 8 or 9.

Citation Information

Patent Citations

  • Thermoplastic polyolefin composition

    CN101010376A

  • Filler masterbatch used for increasing polarity of polypropylene and preparation method thereof

    CN102070833A

  • Injection-molded type TPO (thermoplastic polyolefin) compound for sound-insulating pads for automobiles as well as preparation method of compound

    CN104558840A

  • Antioxidation master batch, and preparation method and application thereof, and automobile interior decoration polypropylene material composed of antioxidation master batch

    CN106633416A

  • Rubber powder based TPO (Thermoplastic Polyolefin) waterproof coiled material and preparation method thereof

    CN108276654A